PENDIDIKAN ANAK USIA SD/MI DALAM PERSPEKTIF AL-QUR’AN SURAT AN-NISA AYAT 9 (Analisis Tafsir Al-Mishbah Karya M. Quraish Shihab) - Mia Muyasaroh; Tanto Aljauharie Tantowie; Sri Meidawaty (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2019)
Education is the determinant of human life, good education will lead to a better standard of life, both from a spiritual and material perspective, without education, humans are just like animals. If we look at the modern era or what is better known as the era of globalization, we have encountered a lot of criminal acts (crimes) committed by a child. Elementary school (SD) children bully their younger siblings, junior high school (SMP) children dare to fight their parents, dare to take belongings of their friends and high school (SMA) children without being embarrassed to be alone with the opposite sex who is not a mahrom, are involved in brawls between students, illegal races, motorcycle gangs, promiscuity, drugs and so on are increasingly troubling parents and society. Therefore, the Al-Mishbah exegesis offers a solution to these problems because the Al-Qur ‟an surah An-Nisa Verse 9 in Al-Mishbah's interpretation of basic education is to build a better generation. The objectives of this study are 1) Knowing the interpretation of Surat An-Nisa verse 9 in Tafsir Al-Mishbah by M. Quraish Shihab, 2) Knowing education for elementary age children in Tafsir Al-Mishbah by M. Quraish Shihab. In this study the authors used a type of library research (library research). The explanation in this scientific paper uses the Content Analysis method, which is research that is in-depth discussion of the content of written information in printed media. The source of the data in this study, the writer got through the research library (literature review), the author collected a number of books, interpretations and scientific works that explain the letter An-Nisa verse 9. The data source used is the data source of the data. primary (Tafsir Al-Mishbah) or secondary data or from libraries, journals or others. The data collection technique carried out by the author is documentation, namely by collecting materials and data through reading and examining interpretations, books, journals and other information materials. While the author's data analysis techniques through the following steps: data interpretation, categorization and data processing. The results of this study found that in the Al-Qur ‟an Surat An-Nisa verse 9 according to the interpretation of Al-Mishbah by M. Quraish Shihab as follows: First, that this verse is related to the responsibility of parents towards future generations which are material in nature. But in verse 9 it is implied that the responsibility towards offspring is not only material, but also immaterial such as education and cultivation of piety. Second, the concept of education contained in the letter An-Nisa verse 9 states that parents have a duty and responsibility to educate their children so that the attitudes and behavior and personality of children in the future will be better; implementation of piety for parents in educating children, as well as; educational methods that must be done by parents in educating children.